Gain and noise figure improvements in a shorter wavelength region of EDFA using a macrobending approach - Daud, S. A.; Yusoff, N. M.; Mohamed, K. S.; Aminudin, L.; Abdul-Rashid, H. A.; Mokhtar, M. R.; Yusoff, Z.; Rahman, F. A. (SP MAIK Nauka/Interperiodica, 2008)
Gain and noise figure improvements are demonstrated in a shorter wavelength region of a double-pass EDFA using a macrobending approach. The EDF is wound in a small radius to suppress the amplified spontaneous emission at the longer wavelength in order to achieve a high amplification in the shorter wavelength. Gain enhancements of about 12-14 dB are obtained with macrobending at the wavelength region between 1480 and 1530 nm. The macrobending also reduces the noise figure of the EDFA at wavelengths shorter than 1525 nm with a maximum improvement of 25 dB.